2014
DOI: 10.1007/s40710-014-0021-y
|View full text |Cite
|
Sign up to set email alerts
|

Pollutant Spreading in a Small Stream: A Case Study in Mala Nitra Canal in Slovakia

Abstract: The Water Framework Directive requires as an obligatory goal to achieve and to keep "good water quality" status within the defined period (for Slovakia-up to the year 2015). For surface waters, the main criterion is the ecological and chemical status of the water. Mathematical and numerical modelling allows evaluating various situations of contaminants spreading in rivers (from everyday wastewater disposal through fatal accidents and discharges of the toxic substances) without immediate destructive impact to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…The calibration involved both D and U, as often done in the literature [see e.g. 3,92,40], and the best fit between the experimental data and the analytical solution was obtained through a least squares minimization.…”
Section: Determination Of the Longitudinal Dispersion Coefficientmentioning
confidence: 99%
See 1 more Smart Citation
“…The calibration involved both D and U, as often done in the literature [see e.g. 3,92,40], and the best fit between the experimental data and the analytical solution was obtained through a least squares minimization.…”
Section: Determination Of the Longitudinal Dispersion Coefficientmentioning
confidence: 99%
“…The difficulties associated with the determination of D represent one of the highest sources of uncertainty for hydrodynamic models simulating pollutant transport in streams. Hence, the recommended practice is to carry out field measurements to directly quantify D and then use the gained information to select the most reliable formula among the existing ones or to build a new site-specific formula [4,48,73,92].…”
Section: Introductionmentioning
confidence: 99%
“…The main flaw of the 1D model is that they are not capable of simulating the pollution spreading until the mixing of pollutants across the stream section becomes complete (Velísková et al 2014). Two-dimensional (2D) model seems valid, and therefore, a 2D model was chosen in this study since they can adequately describe the modeled system.…”
Section: Overview Of the Modeling Approachmentioning
confidence: 99%
“…Moreover, the estimated dispersion coefficients through a tracer experiment are valid for only the examined stream segment (Abderrezzak et al 2015). Consequently, numerous studies were conducted to develop empirical formulas for the determination of both the longitudinal and transverse dispersion coefficients (Fischer 1967 Seo and Cheong 1998;Baek and Seo 2013), or sometimes the coefficients are achieved by researcher's own experience (Velísková et al 2014). Detailed and brief reviews and comparison of these empirical formulas can be found in Seo and Cheong (1998) and Baek and Seo (2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, when this is hampered, their existence will be under threat. With the EU bearing this in mind, a Water Framework Directive (WFD) in 2000 was designed to help chart this course [1], [2]. Even at that, it is herculean to find some of the rivers within the EU member states void of some form of effluent discharge.…”
Section: Introductionmentioning
confidence: 99%